Edge: Link Quality Control - Yeo, Siew Ying (2005)
Enhanced Data rate for Global Evolution (EDGE) plays an important role in the evolution toward Wideband Code Division Multiple Access(WCDMA). EDGE can be introduced either as a packet-switched enhancement for general packet radio service (GPRS), known as enhanced GPRS or EGPRS, or as a circuit -switched data enhancement called Enhanced Circuit-Switched Data (ECSD). This dissertation will focus on packet-switched enhancement, EGPRS.